Prescribing trends before and after implementation of an antimicrobial stewardship program. Issue 5 (18th March 2013) - Cairns, Kelly A; Jenney, Adam W J; Abbott, Iain J; Skinner, Matthew J; Doyle, Joseph S; Dooley, Michael; Cheng, Allen C
Abstract: Objectives: Antimicrobial stewardship programs are recommended to reduce antimicrobial resistance by reducing inappropriate use of antimicrobials. We implemented an antimicrobial stewardship program and aimed to evaluate its effect on broad‐spectrum antimicrobial use. Design, setting and participants: Observational study with historical control using interrupted time series analysis conducted in a tertiary referral hospital. Hospital inpatients prescribed restricted antimicrobials for non‐standard indications, where approval had expired or without approval. Intervention: Baseline period of 30 months immediately followed by an 18‐month intervention period commencing January 2011. Main outcome measures: Number and type of interventions made by antimicrobial stewardship team; monthly rate of use of broad‐spectrum antimicrobial agents (in defined daily doses/1000 occupied bed‐days). Results: The antimicrobial stewardship team made 1104 recommendations in 779 patients during the 18‐month intervention period. In 64% of cases, the recommendation was made to cease or de‐escalate the antimicrobial therapy, or to change from intravenous to oral therapy. The introduction of the intervention resulted in an immediate 17% (95% CI, 13%–20%) reduction in broad‐spectrum antimicrobial use in the intensive care unit and a 10% (95% CI, 4%–16%) reduction in broad‐spectrum antimicrobial use outside the intensive care unit. Reductions were particularly seen in cephalosporin and glycopeptide use, although these were partially offset by increases in the use of β‐lactam–β‐lactamase inhibitors. Conclusions: The introduction of an antimicrobial stewardship program, including postprescription review, resulted in an immediate reduction in broad‐spectrum antimicrobial use in a tertiary referral centre. However, the effect of this intervention reduced over time.